Seroprevalence study of hepatitis E virus infection in two districts of the Czech Republic - Straková, P; Kříž, B; Rudolf, I; Hubálek, Z (Epidemiologie, mikrobiologie, imunologie, 2014)
The aim of this work was to retrospectively examine serum samples from 230 people living in two districts in the Czech Republic in year 1989 (Znojmo and Jihlava) for the IgG antibodies against hepatitis E virus (HEV). For examination, commercial ELISA kit DIA.PRO was used and 13 seropositive persons were found, i.e. 5.7% of those examined. The seropositivity rate was higher in women (6.8%) than in men (3.7%), but the difference was not statistically significant. The age of examined persons did not reveal a significant effect on the seropositivity rate: mean age of seropositive subjects was 38.0 years while that of seronegative persons was 39.4 years.
Keywords: séroepidemiologické studie; Hepatitis E; Česká republika; Aged; Retrospective Studies; lidé středního věku; protilátky virové; senioři; Antibodies, Viral; lidé; Adult; Czech Republic; Middle Aged; dospělí; hepatitida E; Enzyme-Linked Immunosorbent Assay; Female; ELISA; Male; ženské pohlaví; Humans; mužské pohlaví; Seroepidemiologic Studies; retrospektivní studie